Scholastic culture in the Hellenistic and Roman eras: Greek, Latin, and Jewish - Adams, Sean A. (Transmissions, 2019)
Frontmatter --Acknowledgements --Contents --Introduction: Themes in Ancient Scholarship /Adams, Sean A. --Scholastic Research in the Archive? Hellenistic Historians and Ancient Archival Records /Coqueugniot, Gaëlle --Circulation of Lexica in the Hellenistic and Early Imperial Period /Hatzimichali, Myrto --'Bookish Places' in Imperial Rome: Bookshops and the Urban Landscape of Learning /Nicholls, Matthew --Towards a Typology of the Ancient Latin Legal Book /Ammirati, Serena --New Readings in the Text of Herodian /Roussou, Stephanie --What does a Linguistic Expert Know? The Conflict between Analogy and Atticism /Dickey, Eleanor --Suetonius the Bibliographer /Marshall, R.M.A. --Translating Texts: Contrasting Roman and Jewish Depictions of Literary Translations /Adams, Sean A. --Rabbis as Intellectuals in the Context of Graeco-Roman and Byzantine Christian Scholasticism /Hezser, Catherine --Bibliography --Subject Index --Author Index --Works Cited